In vitro and in silico evaluation of Centaurea saligna (K.Koch) Wagenitz—An endemic folk medicinal plant. (April 2018) - Zengin, Gokhan; Bulut, Gizem; Mollica, Adriano; Nancy Picot-Allain, Carene Marie; Mahomoodally, Mohamad Fawzi
Graphical abstract: Highlights: Biological and chemical fingerprints of Centaurea saligna were studied. Antioxidant effects were investigated by in vitro methods. Water extract of Centaurea saligna was the most active against tyrosinase. Ethyl acetate extract of C. saligna exhibited the strongest cholinesterases and α-glucosidase. Apigenin binds to α-glucosidase and stabilised via H-bonds and pi-pi stacking. Abstract: Centaurea saligna (K.Koch) Wagenitz is an endemic plant used in Turkish folk medicine as antibacterial, tonic, astringent, choleretic, anti-rheumatic, diuretic, and antipyretic. This study attempts for the first time to assess the possible enzyme inhibitory potential, antioxidant activity, and determine the phytochemical profile of the ethyl acetate, methanol, and water extracts of C. saligna . The water extract had the highest phenolic content (30.18 mg GAE/g extract) and the most potent oxidant scavenging activity ((120.53, 111.90, 68.43, and 157.88 mg TE/g extract, for CUPRAC [cupric reducing antioxidant capacity], FRAP [ferric reducing antioxidant power], DPPH [2, 2-diphenyl-1-picrylhydrazyl], and ABTS [2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid] assays respectively)). The water extract (4.16 mg KAE/g extract) also inhibited tyrosinase and contained high level of catechin (214 μg/g extract). Ethyl acetate extract showed potent inhibitory capacity against cholinesterases (2.22 and 2.21 mg GALAE/g extract for acetyl and butyryl cholinesterase, respectively) and α-glucosidase (23.80 mmol ACAE/g extract). High concentration of apigenin (2472 μg/g extract) was identified in the ethyl acetate extract. In silico studies showed that apigenin binds to the enzymatic pocket of α-glucosidase and is stabilised by a network of hydrogen bonds and pi-pi stacking. Data collected in the present study advocates the need for further investigation geared towards validation of C. saligna for the management of complications related to the target enzymes, such as diabetes type II, Alzheimer's disease, and epidermal hyperpigmentation.